Crystalline silicon growth on aluminum substrate for photovoltaic application. Issue 10 (19th July 2017) - Bellanger, Pierre; Shivarudraiah, Sunil Benachigere; Leuvrey, Cedric; Dinia, Aziz; Schmerber, Guy; Jomard, Francois; Ulyashin, Alexander G.; Fix, Thomas; Roques, Stéphane; Mugler, Florian; Slaoui, Abdelilah
Abstract : In this work, we investigate the direct formation of crystalline silicon thin films using ECR‐PECVD process on aluminum substrates for solar cells applications. The aluminum substrate offers the advantages of being flexible and highly reflective in addition to serve as the back contact for the cell device. The substrates were pure aluminum or silicon rich aluminum sheets. Monocrystalline silicon substrates were used as reference substrates. Silane and hydrogen were used as precursor gases. Silicon growth was done at different substrate temperatures. The grown silicon films were characterized by Raman spectroscopy, SIMS and XRD techniques. Silicon thicknesses between 230 and 1370 nm were obtained on different types of aluminum substrates. The analyses show that the grown silicon films formed at 480 °C under SiH4 : 40 sccm and H2  = 10 sccm are amorphous silicon at the initial stage and become nanocrystalline (nc‐Si:H) as the deposition proceeds. The crystalline fraction of those films extracted from Raman spectra is found around 40–60% and XRD analysis shows grain silicon size between 41 and 83 Å. Finally, SIMS analysis have revealed graded doping distribution profiles which is indicative of the formation of a nc‐Si:H(i)/nc‐Si:H (p + )/Al substrate, well suited for solar cell structures.